Lembaga Inspirasi Al-Qur’an (LIA): Analisis Sejarah, Strategi Sosialisasi Dakwah, dan Kolaborasi Intelektual dalam Mengembangkan Literasi Tafsir - Qurrata Aini; M. Aziz Zulhijan; Nafisah Ajami; Miftah Fauzan Azimah; Fani Sefriani; Nine Chintya Ayu Inasti; Dewi Wahyu Sejati; Nuraisah Simamora (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the existence and strategic role of the Lembaga Inspirasi Al-Qur’an (LIA) in transforming media-based da'wah into a global tafsir literacy movement. Using a qualitative descriptive approach with data collection techniques through participant observation, in-depth interviews, and digital documentation, this study explores how LIA addresses the challenges of religious literacy among urban communities. The research findings indicate that LIA has successfully developed an integrated da'wah model that combines three main pillars: broadcasting media through the